Pengaruh Meningkatnya Harga Cabai Terhadap Penawaran di Pasar Tradisional Sambu - Nadhifah Rahmallah Sari Nasution; Indah Mawarni; Nur Laili Hasanah; Yenni Samri Julianti Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Chili is an important horticultural commodity with high price volatility that directly affects economic activities in traditional markets. This study aims to analyze the effect of rising chili prices on the supply quantity offered by traders at Sambu Traditional Market, Medan City, and to examine the applicability of the law of supply to perishable agricultural commodities. The research employs a quantitative approach with a descriptive associative method. Data were collected through direct interviews with three chili traders selected using purposive sampling. The results indicate that an increase in chili prices leads to a decrease in supply, with stock reductions ranging from 30 to 60 percent compared to normal conditions. This decline is driven by reduced consumer purchasing power, higher risk of losses due to unsold perishable goods, and disruptions in supply and distribution. These findings suggest that the law of supply does not fully apply to chili commodities due to external factors and the perishable nature of the product. Therefore, maintaining stable supply and efficient distribution is crucial to ensuring market balance in traditional chili markets.